1963
DOI: 10.1085/jgp.46.5.1047
|View full text |Cite
|
Sign up to set email alerts
|

Schwann Cell and Axon Electrical Potential Differences

Abstract: In fifty-seven resting nerve fibers of the squid Sepioteuthis sepioidea impaled from outside to inside, three potential difference (PD) levels were recorded. In twelve nerve fibers the position of the tip of the micropipette, when it was recording one of the I'D levels, was labeled with carmine, and the minute spot of dye was localized histologically. The first t,D level of --10 to --26 my, was located in the endoneurium cells; the second level, formed by a single PD of --33 to --46 mv, was located in the Schw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1972
1972
1990
1990

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In all cases, the axon membrane potential was continuously monitored. In confirmation of Villegas et al (1963) it was found that a single impulse produces little or no detectable change in membrane potential of the Schwann cell.…”
Section: Estimation Of Cellular Surface Areasmentioning
confidence: 88%
See 2 more Smart Citations
“…In all cases, the axon membrane potential was continuously monitored. In confirmation of Villegas et al (1963) it was found that a single impulse produces little or no detectable change in membrane potential of the Schwann cell.…”
Section: Estimation Of Cellular Surface Areasmentioning
confidence: 88%
“…The experimental procedure utilized to measure the electrical potential differences across Schwann cell membrane and across the axon membrane was similar to that described and discussed in previous works (Villegas et al 1963;Villegas, Villegas & Gim6nez, 1968).…”
Section: Experimental 8olutto8mentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental procedure utilized to measure the electrical potential differences across the Schwann cell membrane and across the axon membrane was similar to that described and discussed in previous works (Villegas, Villegas, Gimenez & Villegas, 1963;Villegas, 1972).…”
Section: General Proceduresmentioning
confidence: 99%
“…A great deal of electron-microscopic studies have been made on the giant nerve fibers from several species of squid [1,5,10]. Investigation of the ultrastructure of axons from Dosidicus gigas carried out by Villegas [8] stated that the Schwann layer is formed by a single row of Schwann cells crossed by channels.…”
mentioning
confidence: 99%